Pengaruh fraksi volume pada komposit serat kulit jagung dengan matriks polyester terhadap kekuatan tarik sebagai bahan baku industri papan - Ramadhani, A.; Prastowo, S.H.B.; Handayani, R.D. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
Corn is one of the important crops in Indonesia. Corn crop yields produce waste that is underutilized by the community, one of which is corn husks. Innovation in the field of engineering introduces composite materials consisting of reinforcement and fasteners. Corn husk fibre contains 38% cellulose, which serves as a reinforcement for composite materials. The use of composite materials continues to be developed to meet the community’s need for wood raw materials which is decreasing every year. This study aims to obtain the maximum tensile strength of corn husk and polyester matrix composite materials with volume fractions of 2%, 4%, 6%, 8%, and 10%. The method in this study is an experiment, starting from the corn husk soaking process, adding 5% NaOH, printing specimens to testing the tensile strength with Universal Testing Machine (UTM) HT-2402. All tensile strength test results are following the JISA5905-2003 board industry standard with the highest tensile test at a 4% volume fraction of 26.84 MPa.